Pre-ESRD Care and Mortality in Incident ESRD Patients With Multiple Myeloma. (April 2018) - Cobb, Jason; Plantinga, Laura; Luthi, Jean-Christophe; Lynch, Janet R.; Huff, Edwin D.; Mohan, Sumit; McClellan, William M.
Abstract : Objectives: The relationship between mortality and pre-ESRD (end-stage renal disease) nephrology care in incident ESRD patients with multiple myeloma (MM) as the primary cause of renal failure has not been examined. Materials and Methods: Among 439, 206 incident US hemodialysis patients with MM as the primary cause of ESRD (June 1, 2005 to May 31, 2009) identified using the US Renal Data System, adjusted odds ratios (OR) for reported pre-ESRD nephrology care for ESRD due to MM (n=4561) versus other causes (n=434, 645) were calculated. The association of pre-ESRD nephrology care with subsequent mortality in MM-ESRD patients was examined. Results: MM-ESRD patients were less likely to have any predialysis nephrology care in the year before initiation of dialysis (34.8% vs. 58.5%; OR=0.38; 95% confidence interval [CI], 0.34-0.43) compared with patients with ESRD due to other causes. MM-ESRD patients compared with others were more likely to have catheters on first dialysis (91.8% vs. 75.6%; OR=4.15; 95% CI, 3.54-4.86). Incident MM-ESRD patients receiving predialysis care for ≥6 months had significantly lower 1-year mortality (hazard ratio 0.89; 95% CI, 0.82-0.97 and 0.88; 95% CI, 0.80-0.96, respectively), relative to those without this care. A catheter for dialysis access was associated with a 1.6-fold increase in 1-year mortality in incident MM-ESRD (hazard ratio 1.55; 95% CI, 1.32-1.83). Conclusions: MM-ESRD patients were less likely to have predialysis nephrology care and more likely to use catheters on first dialysis. However, predialysis care is independently associated with lower mortality in MM-ESRD patients. Predialysis care should be prioritized in MM patients approaching ESRD.